Ethical issues in domestic building performance evaluation studies. Issue 3 (3rd April 2019) - Sharpe, Tim
ABSTRACT: Dwellings are occupied by people and it would seem reasonable to expect that the way they are designed and constructed protects people's health and wellbeing, and the effectiveness of this would be verified in practice. However, the construction sector is unusual in that is does not routinely evaluate the performance of its artefacts. Thus, when new forms of construction or technology are used, occupants are effectively the subjects of experiments, which raises ethical concerns. Building performance evaluation (BPE) is a critical tool that addresses this problem. This has mainly been conducted by academic organizations, but to be effective BPE needs to become more widely used by design and construction professionals. In these studies occupant behaviour is a key factor and, consequently, occupants are often the focus of studies. Domestic environments are particularly contentious due to the personal and sensitive data that may be collected. Some of the common ethical issues arising from BPE studies in housing are considered. It is argued that if BPE is to become more widely used by industry professionals and their clients, then a wider adoption of ethical policies is needed to protect the participants of such studies, and the practice of BPE itself.